A Resilient Health System in Response to Coronavirus Disease 2019: Experiences of Turkey - Keskinkiliç, Bekir; Shaikh, Irshad; Tekin, Ahmet; Ursu, Pavel; Mardinoglu, Adil; Mese, Emine Alp (Frontiers in Public Health, 2021)
Turkey's response experience thus far with the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic affords the globe and the region a unique opportunity for and distinctive insights into combating this novel virus. The country's pandemic response, having one of the lowest case fatality ratio (2.8%; 52.5 infections/million population), particularly among the elderly (the high-risk group), rising to the occasion to shoulder its long-standing role in global solidarity and humanitarian support by providing personal protective equipment (globally scarce) to many countries in their desperate time of fight against the pandemic while also meeting its own critical domestic needs, stands out. This paper aims to highlight key decisions, actions, and partnerships behind Turkey's successful fight against the SARS-CoV-2 pandemic that have enabled the country to turn the corner, as well as the components of its success story.